2017
DOI: 10.1107/s2052520617009234
|View full text |Cite
|
Sign up to set email alerts
|

In-house time-resolved photocrystallography on the millisecond timescale using a gated X-ray hybrid pixel area detector

Abstract: With the remarkable progress of accelerator-based X-ray sources in terms of intensity and brightness, the investigation of structural dynamics from timeresolved X-ray diffraction methods is becoming widespread in chemistry, biochemistry and materials science applications. Diffraction patterns can now be measured down to the femtosecond time-scale using X-ray free electron lasers or table-top laser plasma X-ray sources. On the other hand, the recent developments in photon counting X-ray area detectors offer new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…At higher temperatures, the balance of excitation and decay leads to a temperature-dependent steady-state population of the metastable isomer, which can be probed by collecting structures while the sample is under continuous illumination. One could also envisage using synchrotron radiation and fast detectors to perform pump–probe X-ray diffraction experiments, although such experiments have so far been confined to measurements of carefully chosen Bragg reflections rather than complete data sets …”
Section: Responsive Molecular Solidsmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher temperatures, the balance of excitation and decay leads to a temperature-dependent steady-state population of the metastable isomer, which can be probed by collecting structures while the sample is under continuous illumination. One could also envisage using synchrotron radiation and fast detectors to perform pump–probe X-ray diffraction experiments, although such experiments have so far been confined to measurements of carefully chosen Bragg reflections rather than complete data sets …”
Section: Responsive Molecular Solidsmentioning
confidence: 99%
“…One could also envisage using synchrotron radiation and fast detectors to perform pump−probe X-ray diffraction experiments, although such experiments have so far been confined to measurements of carefully chosen Bragg reflections rather than complete data sets. 220 It is typically found that the population of the metastable state α MS (t) during excitation and decay follows Johnson-Mehl-Avrami-Kolmogorov (JMAK) kinetics:…”
Section: Responsive Molecular Solidsmentioning
confidence: 99%
“…2); this is expected, since such a crystallographic axis is parallel to the direction of the applied field E. As we discuss later on, some structure becomes unstable for field values beyond a certain threshold which depends on the material; for those values, the lattice parameters correspond to a transient configuration which belongs to a geometric path connecting two stable states. Such transient configuration can be detected by time-resolved crystallography techniques, capable to monitor structural changes occurring in very short time scales [61][62][63]. Concerning the phonon structure, we observe that an increase of the field produces a general hardening of the − A modes together with a softening of some sliding branches, which may become unstable beyond some critical E (E = |E|) value specific of the system.…”
Section: Resultsmentioning
confidence: 89%
“…In turn, the gating-detector technique was applied in the study of the sodium nitroprusside, Na 2 [Fe(CN) 5 NO]•2H 2 O, single crystals [85]. In this case the NO ligand in the examined compound undergoes significant distortion in the crystal upon irradiation.…”
Section: Case Studiesmentioning
confidence: 99%